The Role of Metacognitive Skills in Music Learning and Performing: Theoretical Features and Educational Implications - Concina, Eleonora (Frontiers in Psychology, 2019)
Metacognition is a key component of musical performance. Metacognitive knowledge and skills are fundamental for musicians at all stages of their academic and professional career to allow them to structure, monitor, assess and, if needed, revise practice sessions towards specific performance goals. Research in music education has highlighted the impact that metacognition has on enhancing musical performance and the learning processes that characterize it. Expert musicians usually show a high level of metacognitive competence, which allows them to effectively self-regulate their learning activity while preparing for a performance. While professional musicians seem to have a wide range of learning strategies and skills, music students are not always aware of the importance of adopting a metacognitive approach in their learning process. In addition, the metacognitive dimension is not always explicitly addressed during music lessons, leaving students to adopt inefficacious learning strategies or to repeatedly use sets of strategies in an incorrect manner. The aim of the current paper is to present and discuss the most recent studies on metacognition in music performance from an educational perspective that focuses on process as well as results. The role of metacognitive competence in musical activity will be discussed, first by examining the components of the metacognitive competence exhibited by expert musicians and then by focusing on the impact of metacognition on music students’ learning. Educational implications for enhancing the learning experience of young musicians will also be discussed.